Prionochaeta opaca - Majka, Christopher; Langor, David (Zenodo, 2008)
Prionochaeta opaca (Say, 1825) NEW BRUNSWICK: Carleton Co.: Meduxnekeeg Valley Preserve, 46.19°N, 67.68°W, 7.IX.2004, R.P. Webster, mixed forest, rotting fungi, (1, RWC). NOVA SCOTIA: Antigonish Co.: Pomquet, 10-17.VII,1998, R.F. Lauff, malaise trap, (1, STFX); Colchester Co.: Debert, 15.VI.1993, 9.VII.1993, 10.V.1994, 21.V.1996, 21.V.1996, J. Ogden, malaise trap, (5, NSNR); Debert, 6.VI.1996, E. Georgeson, malaise trap, (1, NSNR); Halifax Co.: Burnside, 22.V.2003, 23.V.2003, 15.VII.2003, C. Cormier, on dead pig, mixed forest and open areas, (3, SMU); Inverness Co.: Lone Shieling, Cape Breton Highlands National Park, 18-21.VII.1983, D.E. and J.E. Bright, flight-intercept trap, (1, CNC); Kings Co.: Kentville, 11.V.1961, D.H. Webster, on decaying fox, (3, DHWC); Queens Co.: Caledonia, 15.V.2002, P. Colp, flight-intercept trap, (1, NSNR). PRINCE EDWARD ISLAND: locality information lost, 1974-1983, collector information lost, (2, UPEI). Prionochaeta opaca is newly recorded in New Brunswick, Nova Scotia, Cape Breton Island, Prince Edward Island, and Atlantic Canada (Fig. 11). In many southern localities in the United States this species is found in caves where adults and larvae feed on the guano of insectivorous bats. In more northern regions, it is found in forested habitats (Peck and Cook 2002). In Nova Scotia, it has been collected on rotten fungi and mammal carrion. : Published as part of Majka, Christopher & Langor, David, 2008, The Leiodidae (Coleoptera) of Atlantic Canada: new records, faunal composition, and zoogeography, pp. 357-402 in ZooKeys 2 (2) on page 392, DOI: 10.3897/zookeys.2.56, http://zenodo.org/record/576397 : {"references": ["Peck SB, Cook J (2002) Systematics, distributions, and bionomics of the small carrion beetles (Coleoptera: Leiodidae: Cholevinae: Cholevini) of North America. The Canadian Entomologist 134: 723 - 787."]}